2D Echocardiographic features in low T3 syndrome in chronic heart failure - Kumar, Arun; Shivamurthy, YL; Kumar, V Mohan; Ramesh, SS; Shankar, AG Ravi; Basavaraju, MM; Yathish, SK; Manjunatha, SM (Asian Journal of Medical Sciences, 2014)
Background: Thyroid abnormalities are common in chronic heart failure. Severity of heart failure rises by several fold in patients with thyroid dysfunction. Objectives: The purpose of this prospective study is to determine the correlation between low T3 syndrome and chronic heart failure with 2D echocardiography features & predicting the severity of chronic heart failure. Methods: In this descriptive, prospective cross sectional study, all patients who presented to the department of medicine with chronic heart failure during this study period of 12 months from January 2010-December 2011 in K.R.Hospital, Mysore were included. Patients were grouped into Low T3 chronic heart failure, hypothyroid chronic heart failure and chronic heart failure. Results: Mean age of low T3 chronic heart failure patients was higher than other two groups [60.50±6.15(SD) years, Systolic dysfunction on 2D Echo was more in low T3 dilated cardiomyopathy (20%), Diastolic dysfunction on 2D Echo was more in low T3 dilated cardiomyopathy group (30%), Pericardial effusion was seen in more number of patients with low T3 dilated cardiomyopathy (10%). Global hypokinesia was seen in more number of patients with low T3 dilated cardiomyopathy (30%). Segmental hypokinesia was seen in more number of patients with low T3 dilated cardiomyopathy (3%). Mean ejection fraction was seen in more number of patients with low T3 dilated cardiomyopathy [36.78±5.08 (SD) %]. Mean ejection fraction was lower in low T3 dilated cardiomyopathy [34.8±3.293 (SD) %].The high pulmonary artery systolic pressure was seen in more number of patients in low T3 dilated cardiomyopathy (70%). Conclusion: There is significant percentage of chronic heart failure patients having low T3 alone as biochemical parameter. It is important to recognize patients with chronic heart failure as it is associated with increased severity of heart failure. Asian Journal of Medical Science, Volume-5(3) 2014: 35-39 http://dx.doi.org/10.3126/ajms.v5i3.9522